The relationship between good records management and the strength of the organization service / Erratul Shela Eshak...[et al.] - Eshak, Erratul Shela; Mohd Jidi, Munirah; Zakirai@Zakaria, Norlida (2014)
Thestudy was conducted to investigate the relationship between good records management and the strength of the organization service in Dungun Public Municipal (MajlisPerbandaran Dungun). The objective is to identify the relationship between risk management, personnel knowledge, efficient tools and storage and organization service. This study is based on survey respondents taken from a sample size of 180 staffs from different departments at Dungun Public Municipal (MajlisPerbandaran Dungun) that has been selected randomly. Majority respondents agreed that there is relationship between three independent variables and the strength of the organization service. The finding shows that the most important factors that influence to good records management is personnel knowledge. It is anticipates that this study would improve their records management practices to be more effective and contribute to good organization service